The end of British politics? - Moran , Michael (Palgrave Macmillan, 2020)
Contents: Introduction: Imagining and Reimagining `Britain' -- State Created -- A Providential People -- A Messianic State -- Providentialism Without Religion -- Triumph of the Metropolitan British State -- Social Citizenship and British Identity: Providentialism Without Empire -- Statecraft and State Mission -- Notes -- State in Decay -- Decay of British Social Citizenship -- Decay of the Metropolitan Elite -- Decay of the World State -- Decay of the Unionist Settlement -- Inventing and Reinventing the State -- Notes -- State Recreated -- Creative Statecraft and the Reinvention of Britain -- Recasting the Post-War Settlement -- Reshaping State -- Civil Society Relations -- Reshaping the Constitution -- Recreating British Identity -- Statecraft and the Recreation of the State -- Notes -- End of the State? -- Millennium as a Climactic Moment -- Crisis of the British Economy -- Crisis of the British Party System -- Sundered Union and the Crisis of Providentialism -- Waking from a Nightmare -- Notes.